2022
DOI: 10.1109/access.2022.3218322
|View full text |Cite
|
Sign up to set email alerts
|

Clothes Retrieval Using M-AlexNet With Mish Function and Feature Selection Using Joint Shannon’s Entropy Pearson’s Correlation Coefficient

Abstract: The online retrieval of images related to clothes is a crucial task because finding the exact items like the query image from a large amount of data is extremely challenging. However, large variations in clothes images degrade the retrieval accuracy of visual searches. Another problem with retrieval accuracy is high dimensions of feature vectors obtained from pre-trained deep CNN models. This research is an effort to enhance the training and test accuracy of clothes retrieval by using two different means. Init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 68 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The specific structure of DWConv is shown in Figure 2 , which is a combination of depthwise convolution and pointwise convolution, with a low parameter quantity and calculation cost. In addition, the selection of the activation function in the convolution operation has a certain impact on the detection performance inspired by the literature [ 37 ]. We replace the LeakyReLU [ 38 ] activation function in the convolution layer with SiLU [ 39 ] with good generalization ability, whose expression is defined as follows: where is a constant or trainable parameter.…”
Section: Methodsmentioning
confidence: 99%
“…The specific structure of DWConv is shown in Figure 2 , which is a combination of depthwise convolution and pointwise convolution, with a low parameter quantity and calculation cost. In addition, the selection of the activation function in the convolution operation has a certain impact on the detection performance inspired by the literature [ 37 ]. We replace the LeakyReLU [ 38 ] activation function in the convolution layer with SiLU [ 39 ] with good generalization ability, whose expression is defined as follows: where is a constant or trainable parameter.…”
Section: Methodsmentioning
confidence: 99%
“…In 2022 Murtaza, M., et al, [13] had suggested that M-AlexNet can extract more features with its maximum capacity for information, enhancing training and testing accuracy. The CIFAR-10 dataset is used to train the M-AlexNet with Mish using the SoftMax classifier.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To analyze the correlation between the input features and the output results, we conducted an experiment using statistical measures such as the p-value and Pearson correlation coefficient. A p-value smaller than 0.05 indicates a statistically significant difference in organization time among different obstacle quantities [51], [52], [53]. The Pearson correlation coefficient measures the linear correlation between two variables, ranging from −1 to 1, where 1 represents a perfect positive correlation, −1 represents a perfect negative correlation, and 0 indicates no linear correlation.…”
Section: A Correlation Analysis Between Input Feature Matrix and Outp...mentioning
confidence: 99%